A rare case of a unique single ostium coronary artery from the right coronary sinus with anomalous left circumflex course - Zakaria Qechchar; Rime Benmalek; Salim Arous; Mohamed El Ghali Benouna; Rachida Habbal (PAMJ Clinical Medicine, 2020)

(untitled)
Among congenital coronary artery anomalies (CAA), the single coronary ostium is a very rare angiographic finding. Anomalous origin of the left anterior descending artery (LAD) arising from the right coronary artery (RCA) is an extremely uncommon variant of single coronary artery. In most cases, these anomalies are incidental finding with no clinical significance; however, it can cause angina, myocardial ischemia and sudden depending on the relation of the anomalous left coronary artery to the aorta and pulmonary artery. We report the case of a 66-year-old woman with a history of hypertension, diabetes type 2 and hypercholesterolemia who presented with unstable angina associated with New York Heart Association (NYHA) II dyspnea. She underwent coronary angiography that showed both right coronary artery (RCA) and left circumflex artery (LCx) originating from the same ostium in the right sinus of Valsalva (RSV) and an ectopic left anterior descending artery (LAD) arising from the proximal part of the RCA. Gated cardiac computed tomography (CT) confirmed these findings and showed no course between the aorta and pulmonary artery, therefore, surgery was not performed. Diagnosis and management of patients with this coronary anomaly are discussed.